Studi Perencanaan Bendung (Studi Kasus Bendung Kayuangin Kabupaten Majene Provinsi Sulawesi Barat) - Ahmad Adhyaksa; Zulkifly; M. Agussalim; Mahmuddin (Jurnal Karajata Engineering, 2025)
Water is a vital resource that supports various aspects of life, including domestic needs, agriculture, industry, and environmental conservation. The development of infrastructure such as dam plays a key role in maintaining the sustainability of water resources. So it is necessary to pay attention to hydrological analysis, lighthouse, and also stability of a weir. The aim of this research is to be able to understand and know how to plan weir by using existing technical data on weir designs as a guide and as a comparison parameter in this research. This research was carried out in Majene Regency, West Sulawesi Province during March to August 2024. The results of this research show that in general the hydraulic planning review for Kayuangin weir consists of a lighthouse height of 5 m, a weir width of 108 m, an effective width of the weir of 99,5 a deckzerk elevation of 26,59, a lighthouse elevation of 23,20, front floor elevation 17,95, and front floor length 20,60.